Use of Multisystemic Therapy to Improve Regimen Adherence Among Adolescents With Type 1 Diabetes in Chronic Poor Metabolic Control: A randomized controlled trial - Ellis, Deborah A; Frey, Maureen A; Naar-King, Sylvie; Templin, Thomas; Cunningham, Phillippe; Cakan, Nedim (Diabetes care, 2005)
OBJECTIVE:--The aim of this study was to determine whether multisystemic therapy (MST), an intensive, home-based psychotherapy, could improve adherence and metabolic control and decrease rates of hospital utilization among adolescents with chronically poorly controlled type 1 diabetes. RESEARCH DESIGN AND METHODS--A randomized controlled trial was conducted with 127 adolescents with type 1 diabetes and chronically poor metabolic control (HbA[subscript 1c] [A1C] [>/=]8% for the past year) who received their diabetes care in a children's hospital located in a major Midwestern city. Participants randomly assigned to MST received treatment for [approximately]6 months. Data were collected at baseline and at 7 months posttest (i.e., treatment termination). Changes in A1C adherence, as measured by semistructured interviews and blood glucose meters and hospital admissions and emergency department visits, were assessed. RESULTS:--In intent-to-treat analyses, participation in MST was associated with significant improvements in the frequency of blood glucose testing as assessed by blood glucose meter readings (F[1,125] = 16.75, P = 0.001) and 24-h recall interviews (F[1,125] = 6.70, P = 0.011). Participants in MST also had a decreasing number of inpatient admissions, whereas the number of inpatient admissions increased for control subjects (F[1,125] = 6.25, P = 0.014). Per protocol analyses replicated intent-to-treat analyses but also showed a significant improvement in metabolic control for adolescents receiving MST compared with control subjects (F[1,114] = 4.03, P = 0.047). CONCLUSIONS:--Intensive, home-based psychotherapy improves the frequency of blood glucose testing and metabolic control and decreases inpatient admissions among adolescents with chronically poorly controlled type 1 diabetes.